2019 The State of Food Security and Nutrition in the World: Safeguarding Against Economic Slowdowns and Downturns - Torero, Máximo (2019)
Máximo Torero SPECIAL EVENT Discussion on the Key Findings of FAO’s 2019 State of Food Security and Nutrition in the World Report Co-Organized by FAO North America and IFPRI JUL 18, 2019 - 12:15 PM TO 01:45 PM EDT